Emerging insights into the molecular and cellular basis of glioblastoma - Dunn, Gavin P.; Campos, Benito (Genes & development, 2012)
Glioblastoma is both the most common and lethal primary malignant brain tumor. Extensive multiplatform genomic characterization has provided a higher-resolution picture of the molecular alterations underlying this disease. These studies provide the emerging view that “glioblastoma” represents several histologically similar yet molecularly heterogeneous diseases, which influences taxonomic classification systems, prognosis, and therapeutic decisions.
Gesehen am 28.03.2019